2000
DOI: 10.1128/aem.66.6.2422-2429.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Salinity Stress on Growth and Lipid Composition of Shewanella gelidimarina

Abstract: The maximum growth temperature, the optimal growth temperature, and the estimated normal physiological range for growth of Shewanella gelidimarina are functions of water activity (a w ), which can be manipulated by changing the concentration of sodium chloride. The growth temperatures at the boundaries of the normal physiological range for growth were characterized by increased variability in fatty acid composition. Under hyper-and hypoosmotic stress conditions at an a w of 0.993 (1.0% [wt/vol] NaCl) and at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 39 publications
5
45
1
2
Order By: Relevance
“…Seawater caused an increase in the stroma and damaged of chloroplast membranes. The rounding of chloroplasts was attributed to the increase in the volume of the stroma and disorganization of the thylakoid membranes [13].The same observations were also reported by some authors (Liu et al [26], Mitsuya et al [27]). The concentrations of 10% or 25% seawater at 21 days post-anthesis in Gemmieza-9 caused pronounced swelling of the thylakoid membranes in chloroplasts.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Seawater caused an increase in the stroma and damaged of chloroplast membranes. The rounding of chloroplasts was attributed to the increase in the volume of the stroma and disorganization of the thylakoid membranes [13].The same observations were also reported by some authors (Liu et al [26], Mitsuya et al [27]). The concentrations of 10% or 25% seawater at 21 days post-anthesis in Gemmieza-9 caused pronounced swelling of the thylakoid membranes in chloroplasts.…”
Section: Discussionsupporting
confidence: 76%
“…In this connection, Torzilli [12] found that, salt stress increased the cellular concentrations of glycerol in Aureobasidium pullulans. Nichols et al [13] found that in Shewanella gelidimarina, under hyper-osmotic and hypo-osmotic stress conditions, an increase in the proportion of saturated fatty acids was accompanied with increasing salinity level.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in environmental temperature adversely change membrane fluidity, leading bacteria to make compensatory alterations in the degree of saturation of membrane fatty acids (4,20,27,28) to reestablish ideal states of membrane fluidity. Loss of ideal states of membrane fluidity may have an impact on membrane receptor and signaling activities, reducing the rates and efficacy of binding of antibiotics (29,35) and their import or export through bacterial membranes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in environmental temperature adversely change membrane fluidity, leading bacteria to make compensatory alterations in the degree of saturation of membrane fatty acids (4,20,27,28) to reestablish ideal states of membrane fluidity. Loss of ideal states of membrane fluidity may have an impact on membrane receptor and signaling activities, reducing the rates and efficacy of binding of antibiotics (29,35) and their import or export through bacterial membranes (27). On their return to optimum temperature conditions (i.e., removal of temperature stress), bacteria may rebalance the degree of saturation of membrane fatty acids (4,20,27,28) to nonstress conditions, reestablishing optimum membrane structure and function, with a concomitant return to previously observed rates of ABR binding, import, and export.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation